2017
DOI: 10.1159/000484533
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Characterization of a Population of <b><i>Acanthodactylus lineomaculatus</i></b> Duméril and Bibron, 1839 (Reptilia, Lacertidae), from Southwestern Morocco and Insights into Sex Chromosome Evolution

Abstract: Acanthodactylus lineomaculatus is now regarded as an ecotype of A. erythrurus with which it has been recently synonymized. Despite the wide range of A. erythrurus, karyological data for this species are scarce and limited to classical cytogenetic studies carried out in individuals from only 2 locations (central Spain and Spanish enclave of Melilla on the northwestern Mediterranean Moroccan coast). Here, for the first time, we cytogenetically characterized individuals of A. lineomaculatus from the southwestern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…() for L. agilis , and in the W of the Timon species investigated. The enrichment in telomeric‐like repeats of the sex heterochromosome has been recorded also in the lacertid A. lineomaculatus (Giovannotti et al., ), in the agamid lizard Pogona vitticeps (Young, O'Meally, Sarre, Georges, & Ezaz, ), and in the gecko Underwoodisaurus milii (Pokorná, Rens, Rovatsos, & Karatochvíl, ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…() for L. agilis , and in the W of the Timon species investigated. The enrichment in telomeric‐like repeats of the sex heterochromosome has been recorded also in the lacertid A. lineomaculatus (Giovannotti et al., ), in the agamid lizard Pogona vitticeps (Young, O'Meally, Sarre, Georges, & Ezaz, ), and in the gecko Underwoodisaurus milii (Pokorná, Rens, Rovatsos, & Karatochvíl, ).…”
Section: Discussionmentioning
confidence: 89%
“…A, C, TA, CAA, CAG, CAT, GAC, GAG, TAA, TAC) or its centromeric region (repeated motif: CA, GC, GA), whereas in the latter species Giovannotti et al (2017) observed and enrichment in telomeric-like sequences of the W-chromosome heterochromatin. Also in the lacertine Lacerta agilis, the (micro-)W chromosome was found to be enriched in telomeric repeats (Matsubara et al, 2015b;Srikulnath et al, 2014).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, W chromosomes of similar size and repeat content are characteristic for other species of Lacerta : all studied Lacerta species including L. agilis have telomeric repeat accumulation in the W chromosome, and share a monophyletic W-specific subfamily of the IMO-TaqI satellite DNA [Giovannotti et al, 2018]. Considering the fact that the sequence content of the W chromosomes in the related genera Iberolacerta and Timon is different from that of Lacerta , as shown by CGH [Rojo Oróns, 2015], and that the W-specific repetitive DNA can also differ in different populations of the same species [Giovannotti et al, 2017a], the sharing of the same repetitive DNAs by the W chromosomes of different Lacerta species seems to indicate stability and homology for the ZZ/ZW system within this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, W chromosomes of similar size and repeat content are characteristic for other species of Lacerta : all studied Lacerta species including L. agilis have telomeric repeat accumulation on the W chromosome, and share a monophyletic W-specific subfamily of the IMO-TaqI satellite DNA [Giovannotti et al, 2018]. Considering the fact that the sequence content of the W chromosomes in the related genera Iberolacerta and Timon is different from that of Lacerta , as shown by CGH [Rojo Oróns, 2015] and that W-specific repetitive DNA can also be different in different populations of the same species [Giovannotti et al, 2017], the sharing of the same repetitive DNAs by the W chromosomes of different Lacerta species seems to indicate stability and homology for the ZZ/ZW system within this genus.…”
Section: Discussionmentioning
confidence: 99%